The Criminal Law Protection of Personal Property - Olga Aleksandrovna Dolgova (Сибирское юридическое обозрение, 2011)
The article deals with Chapter 21 of the Criminal Code of the Russian Federation, revealed shortcomings in this chapter and proposed measures to improve the penal protection of personal property.